Furan-derived chiral bicycloaziridino lactone synthon: collective syntheses of oseltamivir phosphate (Tamiflu), (S)-pipecolic acid and its 3-hydroxy derivatives - Chavan, Subhash P.; Kadam, Appasaheb L.; Shinde, Shrikrishna S.; Gonnade, Rajesh G. (Chemistry-An Asian Journal, 2020)
A unified synthetic strategy for oseltamivir phosphate (tamiflu), (S)-pipecolic acid, and its 3-hydroxy derivatives from furan derived common chiral bicycloaziridino lactone synthon is described here. Key features are the short (4-steps), enantiopure, and decagram-scale synthesis of common chiral synthon from furan and its first-ever application in the total synthesis of biologically active compounds by taking the advantages of high functionalization ability of chiral synthon.
Keywords: Aziridine synthon; Chiral auxiliary; collective synthesis; Pipecolic acid; Tamiflu

Scalable synthesis of 3-Ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one: an important building block of the antidiabetic drug glimepiride - Chavan, Subhash P.; Pawar, Ambaji A.; Patil, Niteen B.; Kadam, Appasaheb L.; Shinde, Shrikrishna S. (Synthesis-Stuttgart, 2020)
A four-step, practical, and easily scalable synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one, an important building block of the antidiabetic drug glimepiride, has been accomplished. Key features are the synthesis of 3-methyl-4-hydroxy-2-butenolide in water and triflic acid mediated N-benzyl lactam N-deprotection. The main advantages of this process are the scalable synthetic route and decreased number of reaction steps, which paves the way for the industrial-scale synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one.
Keywords: antidiabetic drug; Butenolide; glimepiride; lactams; scalable synthesis